2009
DOI: 10.1111/igc.0b013e3181a40618
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Estrogen and Progesterone Receptor Expression With Connexins 26 and 43 in Endometrial Cancer

Abstract: Progression of numerous neoplasms could involve alterations of gap junction channels composed of connexins (Cxs). Disorders of expression and cellular displacement of Cxs were also found in endometrial cancer. Gap junctional intercellular communication can be regulated by wide array of agents, for instance, growth factors, oncogenes, and steroid hormones. Nevertheless, expressions of Cxs and progesterone receptor (PR) were not compared in human tissues. This study focused on assessment of expression of estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…Most human endometrial adenocarcinomas express progesterone receptor and estrogen receptor alpha, so the relations of connexins with PgR and ER could turn out to be crucial in the development of this cancer [2]. However, there were no relationship between Cx26 and ER or between Cx43 and hormonal receptors in our previous study [2]. Phosphorylation of Cx43 causes deregulation of communication via gap junction channels in endometrium [4].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Most human endometrial adenocarcinomas express progesterone receptor and estrogen receptor alpha, so the relations of connexins with PgR and ER could turn out to be crucial in the development of this cancer [2]. However, there were no relationship between Cx26 and ER or between Cx43 and hormonal receptors in our previous study [2]. Phosphorylation of Cx43 causes deregulation of communication via gap junction channels in endometrium [4].…”
Section: Introductionmentioning
confidence: 72%
“…A Cx26 stimulating property was found in case of the phytoestrogen, genistein [7]. In our previous study only progesterone receptor expression was found to associate with Cx26 and grading in the manner of negative correlation in endometrial cancers, while Cx26 positively correlated with tumor stage [2,8]. In this perspective an eventual impact of connexins on apoptosis is of great importance.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Standard immunohistochemical procedure for STAT3, Cx43, Cx26 ER and PgR was performed in endometrioid adenocarcimonas according to previously described protocols (10,(12)(13). Briefly, endogenous peroxidase activity was blocked with 60 sec treatment of slides 3% hydrogen peroxide (Santa Cruz Biotechnology, Inc. Santa Cruz, CA, USA, and then the slides were exposed to 1.5% normal blocking serum (Dako) for 90 min to inhibit unspecific binding reaction.…”
Section: Methodsmentioning
confidence: 99%